The Impact of Nutrients on Mental Health and Well-Being: Insights From the Literature - Muscaritoli, Maurizio (Frontiers in Nutrition, 2021)
A good nutritional status is important for maintaining normal body function and preventing or mitigating the dysfunction induced by internal or external factors. Nutritional deficiencies often result in impaired function, and, conversely, intakes at recommended levels can resume or further enhance body functions. An increasing number of studies are revealing that diet and nutrition are critical not only for physiology and body composition, but also have significant effects on mood and mental wellbeing. In particular, Western dietary habits have been the object of several research studies focusing on the relationship between nutrition and mental health. This review aims to summarize the current knowledge about the relationship between the intake of specific micro- and macronutrients, including eicosapentaenoic acid, docosahexaenoic acid, alpha-tocopherol, magnesium and folic acid, and mental health, with particular reference to their incidence on stress, sleep disorders, anxiety, mild cognitive impairment, as well as on neuropsychiatric disorders, all significantly affecting the quality of life of an increasing number of people. Overall data support a positive role for the nutrients mentioned above in the preservation of normal brain function and mental wellbeing, also through the control of neuroinflammation, and encourage their integration in a well-balanced and varied diet, accompanied by a healthy lifestyle. This strategy is of particular importance when considering the global human aging and that the brain suffers significantly from the life-long impact of stress factors.